Sex differences and performance evaluation in preschool athletic events - Cvenić, Josip (Annales kinesiologiae (Koper), 2025)
This study examined sex differences in motor performance among preschool children and proposed a preliminary, norm-referenced evaluation scale for selected athletic disci-plines within the Olympic Festival of Kindergartens. The sample consisted of 120 children (60 boys and 60 girls), approximately six years of age, representing the best-performing participants from county-level competitions conducted between 2007 and 2017. Motor performance was assessed in ball throwing, standing long jump, and the 50-m sprint. Sex differences were analysed using the independent samples t-test with effect sizes reported as Cohen’s d. Boys achieved significantly better results in ball throwing (t(118) = 6.51, p < 0.001, d = 1.19) and the 50-m sprint (t(118) = -2.07, p = 0.041, d = -0.38), indica-ting large and small-to-moderate effects, respectively. No significant sex difference was observed in the standing long jump (t(118) = 0.64, p = 0.521, d = 0.12). Comparisons with national datasets revealed similar performance patterns, confirming earlier findings of sex-related differences in explosive strength and speed during early childhood. The proposed five-level evaluation scale, derived from competitive performance distributions, provides a practical assessment framework for use in organized preschool sport settings. Given the selective nature of the sample and the absence of formal psychometric valida-tion, the scale should be considered preliminary and applicable primarily to physically active preschool children participating in competitive events.
Keywords: athletics events; evaluation scale; motor performance; motorične sposobnosti; ocenjevalna lestvica; predšolski otroci; preschool children; razlike med spoloma; sex differences; športni dogodki